Humanising the Energy Transition: Towards a National Policy on Energy Poverty in the Netherlands - Feenstra, Mariëlle; Middlemiss, Lucie; Hesselman, Marlies; Straver, Koen; Tirado Herrero, Sergio (Frontiers in Sustainable Cities, 2021)
Energy poverty is emerging as a national agenda in the Netherlands. Local authority leadership and action on this agenda, and European Union reporting requirements around the energy transition have aligned to create an opportunity to establish a national agenda on this issue. Early action on energy poverty by local authorities stemmed from their recognition of the value of addressing environmental, health, social welfare and poverty goals through measures to address the problem. In contrast, the experiences of vulnerable energy consumers have limited recognition in national policy. Meanwhile EU requirements for climate reporting include a specification for measuring and monitoring energy poverty. This growing momentum has resulted in an emerging interest in energy poverty as a means to achieve a just transition at a national level, as reflected in the Dutch National Climate and Energy Plan. In this paper, we profile the case of the Netherlands, and outline the opportunity we see for the development of an energy poverty agenda in national energy transition policy, as part of a multi-level energy governance effort. We report on a national stakeholder workshop that we led, linking the lived experience of energy poverty in the Netherlands with policy solutions. Following the clear call for a national policy in this workshop, we also outline a strategy for engagement with energy poverty in the Netherlands, published recently in a white paper on this topic.